Kenyamanan Lingkungan Kelas dan Pengaruhnya terhadap Motivasi Siswa Sekolah Dasar - Suhaila Nasywa A; Ibnu Muthi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
A comfortable classroom environment plays a crucial role in supporting effective learning processes at the elementary school level. This comfort includes physical aspects such as lighting, ventilation, cleanliness, and room arrangement, as well as psychological aspects such as peer relationships, teacher approach, and emotional atmosphere in the classroom. When students feel physically and emotionally comfortable, they tend to be more focused, calm, and ready to absorb learning material. A pleasant environment can create a positive learning experience and foster enthusiasm for school activities. This study aims to examine the influence of classroom environmental comfort on elementary school students’ learning motivation. Using a descriptive approach, data were collected through observations and questionnaires that explored students’ perceptions of their classroom conditions. The results show that the more comfortable students feel in their classroom, the greater their motivation to actively engage in learning activities. A supportive classroom atmosphere is proven to enhance learning spirit, participation, and curiosity. Based on these findings, it is recommended that schools pay closer attention to classroom comfort as part of a broader strategy to improve the quality of education at the elementary level.